ANALISIS DAYA SAING DAN DAMPAK KEBIJAKAN PEMERINTAH TERHADAP KOMODITAS KEDELAI VS PENGUSAHAAN KEDELAI DI KABUPATEN LAMONGAN, JAWA TIMUR - Syahrul Ganda Sukmaya; Dwi Rachmina; Saptana Saptana (Forum Agribisnis, 2016)
The low productivity of domestic soybeans to be one of the problems why the national soybean production can not meet the needs of the domestic market. Besides government policy is not optimal and sometimes contradictory in increasing domestic soybean production contributing to the competitiveness of domestic soybeans to soybean imports this time. The purpose of this study was to analyze the level of financial and economic advantages of farming. Analyze the competitiveness of soybean status. Analyzing the impact of government policy on the competitiveness of soybean in Lamongan, East Java. Analyzing sensitivity on the competitiveness of soybean. In this research using policy analysis the matrix ( PAM ) , the results of the analysis this is used for saw two basic indicators measuring competitiveness , namely private cost ratio ( PCR ) , domestic resource cost ratio ( DRCR ) is an indicator the comparative advantages. The sample of the in this research as many as 120 respondents. The analysis showed that soybean cultivation in Lamongan unprofitable and inefficient financially and economically. Based competitiveness indicators that PCR and DRCR, showed that soybean systems in Lamongan not competitive. PCR coefficient values> 1 and DRCR> 1. This means soybean systems uncompetitive and inefficient. Based on indicators of the impact of government policy divergence to the input-output soybean showed that existing government policies detrimental exploitation of soybean farming in Lamongan. Changes in domestic soybean prices by 15 and 20 percent increases the competitiveness of domestic soybean competitive.